Mapping the relationship between alcohol use disorder and gut microbiota: a 20-year bibliometric study - Xiang, Ao; Chang, Yonglong; Shi, Li; Zhou, Xuhui (Frontiers in Microbiology, 2024)
BackgroundAlcohol use disorder (AUD) is a psychiatric disorder that is widespread worldwide. Alcohol use is a significant contributor to the global burden of death, disability and disease. Modulation of the gut microbiota is a promising approach to improve the efficacy and minimize the adverse effects of colorectal cancer treatment. The relationship between the presence of microbes and AUD has been widely validated. However, few studies have examined this relationship using bibliometric methods. Therefore, this study analyzes the research hotspots and trends in human gut microbiology and AUD over the last two decades from a bibliometric perspective. This study aims at provide new directions for basic and clinical research in this field.ObjectiveA comprehensive discussion of the relationship between the current state of research and trends in AUD and intestinal flora.MethodsWe collected publications from the Web of Science Core Collection database from 2003 to 2023 according to established inclusion criteria. We analyzed countries, institutions, authors, and research contributions using CiteSpace, VOSviewer, and Scimago Graphics to visualize research trends in the field.ResultsA total of 2,102 publications were obtained, with a rapid increase in the number of publications since 2016. The United States and China are major contributors to the field and have established a network of partners in several countries. Five hundred ninety-five academic journals published articles on the topic. The author with the highest number of publications is Prof. Bernd Schnabl of the Department of Gastroenterology at the University of California, San Diego. In addition to “gut flora” and “AUD,” high frequency words in the keyword co-occurrence network analysis included alcoholic liver disease, tryptophan metabolism, enterohepatic axis, and fecal microbial transplantation.ConclusionThe results of this study provide a bibliometric analysis and visualization of key research areas in the gut microbiota and AUD over the past 20 years. The results suggest that the role of the gut microbiota in AUD and its potential mechanisms, especially therapeutic targets, should be closely monitored and could become a hot topic in the field.